Uji Sitotoksisitas Ekstrak Pektin Limbah Kulit Buah Kopi Robusta (Coffea canephora) pada Kultur Sel Fibroblas Pulpa Gigi Manusia (Cytotoxicity Effect of Pectin Extract from Coffea Robusta (Coffea canephora) Fruit Peels on Human Dental Pulp Fibroblasts Cel - Kharishah Muslihah; Agus Sumono; Dwi Warna Aju Fatmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Background: Coffee has a by-product (waste product) that generated from coffee processing. Coffee fruit's peels contains active compound, that is pectin. Pectin has several benefits in health, as a regeneration of hard and soft tissue that can be applied in dentistry and pectin has the potential as an anti-cancer substance. Pectin as a biomaterial must have biocompability. Biocompatibility of the material can be tested by cytotoxicity test by MTT method on human dental pulp fibroblasts cell culture. Objective: To know the toxicity of extract pectin from coffee robusta fruit peels on human dental pulp fibroblasts cell culture. Method: This research is a experimental laboratory with post-test only control group design. Culture of fibroblast cells at the well was exposed by pectin extract for 24 hours, then each well was given MTT and incubated for 4 hours. The effects of cytotoxicity were measured by calculating cell viability (%). Data were analyzed using Probit test, One-way ANOVA followed by LSD. Result: Each group has a cell viability value above 50%. Conclusion: Extract pectin from Robusta coffee fruit peel's had no cytotoxic effect on human dental pulp fibroblsts cell culture Keywords: coffe robusta fruit peels, cytotoxicity, human pulp fibroblst cell culture, pectin